'Gadgets and Gurus': Wired magazine and innovation as a masculine lifestyle. Issue 1 (2nd January 2017) - Bødker, Henrik
Abstract : In May 2013, Wired celebrated the magazine's 20th anniversary by restating Louis Rossetto's claim from the first issue that '"[t]here are a lot of magazines about technology". Wired is not one of them' (fromhttp://www.wired.com/magazine/wired-20th-anniversary/ ; accessed on 3 July 2013). This article agrees by arguing that Wired in its formative years also should be seen as a men's lifestyle magazine, which—in contrast to the category's usual focus on fashion, sex and leisure—was characterised by a specific type of anticipatory and utopian engagement with innovation and technology that sought to carve out a better life by breaching the boundaries between work/leisure and writer/reader. By focusing more broadly on technology as 'culture' Wired thus allowed for a negotiation of masculinity premised on both work and production and leisure and consumption and thus a new way of weaving the 'authentic' into the contemporary and digital landscape of consumption.